Shei shi mo fa wang - Cheung, Shana Wan Shan (Xiang gang hui ben wen hua, 2021)
It was the first time for a granddaughter to spend her summer vacation with her grandparents. Her grandpa took her to the swimming pool and her grandmother also learned how to swim with her. In addition to the swimming pool, the grandma also loved swimming in the sea. She could paddle around in it like a fish and it helped ease the pain from her body and her soul.
Keywords: Bilderbuch; Motivation; Alter; Ältere Frau; Beharrlichkeit; Schwimmen; Eigenständigkeit; Freiheit